PENGARUH MANAJEMEN MODAL KERJA TERHADAP KINERJA PERUSAHAAN : STUDI PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TELAH GO PUBLIK DI BURSA EFEK INDONESIA - Silalahi, Donalson; Silalahi, Esli (Jurnal Manajemen dan Bisnis, 2021)
The purpose of this study is to obtain the empirical evidence about the impact of: (a) the average conversion period on company performance. (b) the inventory conversion period on company performance. (c) the average payment period on company performance and (d) the cash conversion cycle on company performance on the Indonesia Stock Exchange. To achieve this goal, research was carried out on manufacturing companies listed on the Indonesia Stock Exchange and the sample size is 48 companies. Thus, the sampling technique in this study used a purposive sampling. The data used in this study is secondary data. All data is obtained from the Indonesia Stock Exchange website. Furthermore, the regression coefficient of each independent variable was tested using the t test and the F test with Î± 10 percent. Referring to the results of research, the following conclusions can be made: First, the average conversion period has a positive and significant effect on company performance. The ability of the average conversion period in explaining the company's performance is 13.4 percent. Second, the inventory conversion period has a positive and significant effect on company performance. The ability of the inventory conversion period to explain the company's performance by 19.4 percent. Third, the average payment period has a positive and insignificant effect on company performance. The ability of average payment period in explaining the company's performance is 0.9 percent. Fourth, the cash conversion cycle has a positive and significant effect on company performance. The ability of the cash conversion cycle to explain the company's performance by 14.7 percent. Fifth, the cash conversion cycle and the quadratic cash conversion cycle can explain the variation in company performance by 23 percent. Sixth, there is no optimal working capital in the companies under study.